Pengujian Beberapa Dosis Pupuk Kandang Jangkrik Terhadap Pertumbuhan Bibit Kakao (Theobroma Cacao L.) - Ivonny Asri; Warnita; Wulan Kumala Sari (Jurusan Budidaya Perkebunan, 2021)
Crickets feces manure is the solid waste produced by cricket metabolism which contains some nutrients. Its application as the mix of planting medium is very potential for increasing plant growth. The objectives of this study were to determine the effect of several doses of crickets feces manure on the growth of cacao (Theobroma cacao L.) seedling and to obtain the best dose of it for growth of cacao seedlings. This research was a Completely Randomized Design (CRD) with 5 treatments and 4 replications to obtained 20 experiment units, and each of it consisted of 3 plants, so there were total 60 plants. The research was carried out in the experimental field of the 3rd Campus Andalas University, Dharmasraya. The observation data were analyzed by analysis of variance (F -test) and continued by the Duncan’s New Multiple Range Test (DNMRT) at 5% level significantly. The results showed that the crickets feces manure contained 2.70% N, 0.56% P, 2.24% K, 10.16% C, 3.76% C/N, 1.47% Ca, 0.69% Mg, and 0,28% Na. Application of crickets feces manure influences the growth of cacao seedlings on the variables of plant height, stem diameter, number of leaves, leaf length, and leaf width. Application of crickets feces manure with a dose of 50 g / polybag is the efficient treatment for the growth of cacao seedlings.